If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -8b = 72 Solving -8b = 72 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-8'. b = -9 Simplifying b = -9

| 5(m+3)=15 | | -6x+7=7 | | -2x=-2 | | 5y=-40 | | -11x-(20)=-97 | | -3-x=-3 | | 9b=-27 | | 7x-17=4x+1 | | 2x+2(3x+4)+5= | | x(2)-64=0 | | -1+2x+2x=35 | | 7v=35 | | m^6=8 | | -9z=45 | | x(x)-64=0 | | 3x+8=2x-17 | | x+9+5x=-63 | | 7(x)(x)-48x-7=0 | | 2+4x-x=2 | | (m)=23 | | 9x+3x=26 | | 15=4+g | | (a)+5=22 | | 35=3+5x | | -8k-7k= | | H+13=81 | | 5f-45=-33-(-3f) | | 12x+3= | | 7=4x-2x+7 | | 1=x+x+1 | | 7x-10-x=-4 | | 3a+2b=3 | | 8c+12=-68 | | 62=5x+x-10 | | 7(x)(x)(-48)x-7=0 | | -3(2x+5)-(x+8)=-17(x-1) | | 324=5252 | | 16(2)(3x)=12x+3 | | 8x+8=4x+16 | | 9a(a)=108 | | x(x-12)+27=0 | | -2(3x-2)= | | n-2=6-3n | | 4y-5=-19-3y | | -2(7x+9)-(6x+1)=-12x-7 | | 30x-11=30 | | m+0.4=3m+0.8 | | 17x-25x= | | 4y-9=y-9 | | 10-4X=9-2X | | 16x-8-9x=27 | | 12-4n=15-n | | 8x-9x=17 | | 0=x^6-7x^4+7x^2+15 | | 16=y+5 | | 7y-91=-6x | | 5-2y=11+4y | | 3(m+4)-5m= | | 12x-2(4x-4)=28 | | 3(X-1)=6 | | -x^6+7x^4=7x^2+15 | | 4=18-3x | | 8y-6y=-28 | | 3x+9=-6 | | a(12a+5)=7 |